Python web penetration testing cookbook : over 60 indispensable Python recipes to ensure you always have the right code on hand for web application testing /: over 60 indispensable Python recipes to ensure you always have the right code on hand for web application testing. (2015) - Buchanan, Cameron; Ip, Terry; Mabbitt, Andrew; (Security test engineer), May, Benjamin; Mound, Dave
No abstract available